Respuesta :

Answer:x=-3

Step-by-step explanation:

Combine like terms

6 + -4x = 7x + -9x + 12

Reorder the terms:

6 + -4x = 12 + 7x + -9x

Combine like terms: 7x + -9x = -2x

6 + -4x = 12 + -2x

6 + -4x = 12 + -2x

Add '2x' to each side of the equation.

6 + -4x + 2x = 12 + -2x + 2x

Combine like terms: -4x + 2x = -2x

6 + -2x = 12 + -2x + 2x

Combine like terms: -2x + 2x = 0

6 + -2x = 12 + 0

6 + -2x = 12

Add '-6' to each side of the equation.

6 + -6 + -2x = 12 + -6

Combine like terms: 6 + -6 = 0

0 + -2x = 12 + -6

-2x = 12 + -6

Combine like terms: 12 + -6 = 6

-2x = 6

Divide each side by '-2'.

x = -3

Simplifying

x = -3

X:5 esa es la respuesta espero te sirva mucho
ACCESS MORE